Terrestrial insect herbivore communities of riparian zone in urban ecological river, Korea - Jeong Ho Hwang; Sung-Yeol Kim; Eunjoong Kim; Joo Hyuk Yoon; Mean-Young Yim; Seung-Lak An (Journal of Asia-Pacific Biodiversity, 2021)
This study was conducted on the association of terrestrial insect herbivore communities with flora and plant communities in the riparian zone of an urban river in Daejeon, Korea. The survey was conducted in May, August, and October on three sites that are composed typical habitat diversity in the river. As a result of the analysis, the highest matching rate of insect herbivore host plant and flora of the site was site 1 with 93%. In addition, the dominant and subdominant species of the terrestrial insect herbivores showed a very close association with the dominant plant species that make up the plant community. As a result of analysis of similarity among the sites, the most heterogeneous group of terrestrial insect herbivore communities were in May, which presumed to be affected by changes in biomass of host plants before and after the rainy season. The results of this study can be used as data necessary for the conservation of biodiversity in riparian zone in the future.